Una deconstrucción del pasado de Israel en el antiguo Oriente: hacia una nueva historia de la antigua Palestina - Pfoh, Emanuel (El Colegio de México, 2010)
Both “ancient Near East” as well as “ancient Israel” are Western historiographical constructs built upon the tenets of European historiography from the nineteenth century. Such terminology, still hegemonic among academic quarters, and the historical pictures it denotes (evolutive and progressive within a line of historical continuity, rather than descriptive and analytical on its own historical situations) conveys interpretative obstacles for a critical his-tory of Near Eastern antiquity when applied uncritically. A truly critical interpretative perspective calls for the deconstruction of the cultural matrix of said concepts and a reconstruction of historical processes from primary sources (archaeology, epigraphy) rather than from secondary sources (the Bible, or better the Old Testament), thus opening new paths towards a critical history of ancient Palestine replacing the histories of “ancient Israel” as the product of an outdated historiographical paradigm.